2018
DOI: 10.3390/rs10091445
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Antarctic Glacier and Ice-Shelf Front Dynamics—A Review

Abstract: The contribution of Antarctica’s ice sheet to global sea-level rise depends on the very dynamic behavior of glaciers and ice shelves. One important parameter of ice-sheet dynamics is the location of glacier and ice-shelf fronts. Numerous remote sensing studies on Antarctic glacier and ice-shelf front positions exist, but no long-term record on circum-Antarctic front dynamics has been established so far. The article outlines the potential of remote sensing to map, extract, and measure calving front dynamics. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 141 publications
(262 reference statements)
0
53
0
Order By: Relevance
“…Lastly, a part of Marie Byrd Land is selected because of the multi-year ice areas. Within this area, the Getz Ice Shelf was also chosen to test our algorithm on time series generation as little is known about the current frontal fluctuations [2]. The Getz Ice Shelf is the largest ice shelf along West Antarctica with an area of 33,395 km 2 and pinned with islands along the front [32].…”
Section: Study Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, a part of Marie Byrd Land is selected because of the multi-year ice areas. Within this area, the Getz Ice Shelf was also chosen to test our algorithm on time series generation as little is known about the current frontal fluctuations [2]. The Getz Ice Shelf is the largest ice shelf along West Antarctica with an area of 33,395 km 2 and pinned with islands along the front [32].…”
Section: Study Areasmentioning
confidence: 99%
“…Only in this way, recent changes in glacier and ice shelf front movement can be detected. Additionally, our understanding of forces controlling calving front location (CFL) change is still limited as continuous Antarctic coastal-change time series are scarce [2]. This is attributed to the lack of suitable amounts of remote sensing imagery and the time-consuming manual delineation of calving fronts.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies [16,20,21] have reported substantial changes in the remnant LBIS, namely the Scar Inlet Ice Shelf (SIIS), and its tributary glaciers during the same time, suggesting that the ice front retreat, ice flow acceleration, and enhanced surface features are key indicators producing its instability. The dynamic behavior of glaciers and ice shelves affects the contribution of the Antarctic ice sheet to global sea level rise, and one important parameter of ice sheet dynamics is the location of glacier and ice shelf fronts [22]. A change in the position of an ice shelf front reflects a change in the stability of that ice shelf to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Baumhoer et al [14] provides an overview of satellite sensors and existing methods used to detect Antarctic glacier and ice shelf front dynamics. Calving fronts of glaciers and ice shelves are in general mapped using Synthetic Aperture Radar (SAR) and optical satellite sensors [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have provided coastlines for selected smaller study regions (for example, [22][23][24][25]). Baumhoer et al [14] consolidated these existing CFL products to map and assess patterns of glacier and ice shelf front changes around Antarctica between 1972/1975 and 2009/2015. They reported difficulties caused by data gaps in time and space, differences in temporal sampling and the variety of different methods necessitating undesirable assumptions.…”
Section: Introductionmentioning
confidence: 99%